O governo Chávez e desenvolvimento: a política em processo - Barros, Pedro Silva (2007)
Based on the concept that Hugo Chávez s government of Venezuela has an economic policy in process and that the Venezuelan economy is markedly rentist, this research discusses the determining factors in the economic and political dynamics of Venezuela during the command of Hugo Chávez. The first chapter discusses the theoretical foundations for the development plan of Venezuela as proposed by Hugo Chávez s government, in particular the concept of Endogenous Development and its practical implications since 2003. First, the evolution of the debate about Latin American development is presented. It begins with the ECLAC s Structuralism theory in the nineteen forties and fifties; passing through the Dependency theory of the sixties and seventies; and, concluding with the discussion of the Endogenous Development concept, conceived during the nineties as a neostructuralist response to the Washington Consensus program. The first chapter also presents Rentist Capitalism and the Dutch Disease as characteristics of the Venezuelan economy. The second chapter discusses the historical importance of oil to the Venezuelan economy and its influence in politics, in particular with respect to the creation of PDVSA, the state-owned petroleum company. It poses the very social and economical history of Venezuela as the basis to the emergence and consolidation of Chavezism, and presents the three basic determining factors that brought Chávez to power: the crisis of the development model, which is not exclusive to Venezuela, but typical of nearly all Latin American economies; the exhaustion of the Rentist Capitalism model; and, the fatigue of the political pact that governed Venezuela for forty years. The third and last chapter is an attempt to comprehend Chávez s economic policy by presenting and discussing four distinct stages of the economic and political plan, from 1999 to present days. At first, the government program is analyzed. Next, the analysis turns to state control by the new administration, by way of the new Bolivarian Constitution of 1999 and the enabling laws of November 2001. The third stage is the government s political inflexion point and the conservative response represented by the oil companies strike. The last stage represents the controlled State, enabled by Chávez s strengthening with the end of the strike and, mainly, his victory in the referendum of 2004